THE EXPRESSION OF ‘INTEREST’ IN THE AMICUS CURIAE PRESENTED BY THE CIVIL SOCIETY BEFORE THE INTERNATIONAL CRIMINAL COURT - Peruana de Derecho Internacional, Sociedad (2020)
In the current stage of Public International Law, access of the individual and organizedcivil society to international courts, just like participation in proceedings is a constant.In particular, through the institution of the amicus curiae, traditionally defined as the‘neutral bystander’ who voluntarily intervenes in a dispute, assisting the court in theresolution of the case. This definition has evolved at the international level, so that insome cases the intervention of amici has been allowed to have an interest in theoutcome of the procedures. However, the expression of interest is not expresslyregarded as a criterion for determining the admission or rejection of amicus curiae inthe rules of international criminal courts. In this sense, the Rome Statute of theInternational Criminal Court is no exception. For this reason, the present paper carriesout a normative and jurisprudential analysis of the legal effects arising from theexpression of interest in the pleadings submitted by civil society to the InternationalCriminal Court.